Leadership in Educational: A Systematic Review - Mehmet Toprak (Har Press Indonesia, 2020)
The aim of this study is to show the extent to which different models of leadership in education are studied, including changes in the trends of research on each model over time, the most prominent scholars working on each model, and the countries in which the articles are based. The analysis of related literature was first conducted using a bibliometric analysis of research and review papers indexed in the Science Database Web between 1980 and 2014. A more in-depth analysis of the selected papers was then carried out using the content analysis method. Results have shown that there has been an increasing interest in educational research leadership models over time. Distributed leadership, educational leadership, teacher leadership and transformational leadership are the most studied leadership models in education research. It was also found that related research increasingly focuses on the impact of leaders on organizational behaviors/conditions and student achievement. As a result, the use of quantitative methodology has increased significantly over the last decade. Possible reasons for such changes, implications and recommendations for future research are also discussed.